Development and validation of Restless Legs Syndrome Diary for the assessment of severity and course of symptoms – A cross-sectional study - Chandni Sharma; Vijay Krishnan; Lokesh Kumar Saini; Niraj Kumar; Ravi Gupta (Indian Journal of Psychiatry)
Background: The clinical course and severity of restless legs syndrome (RLS) are variable. Existing questionnaires measure the severity of RLS based on recall. One possible solution could be the daily charting of symptoms in a diary. Aim: Development and validation of a diary for the longitudinal assessment of symptoms and the impact of RLS. Materials and Methods: This study was conducted in two phases. In phase 1, an RLS diary was developed. During phase 2, it was given to patients presenting with RLS. They were explained how to fill in the information in the diary. It collected information related to symptoms as well as sleep. Adverse effects of the symptoms on mood and daytime function were also assessed. Three scores were calculated from the data—the burden of RLS, the burden of severe RLS symptoms, and the overall burden of RLS. The convergent validity of the diary was calculated by comparing it with the international RLS severity rating scale (IRLS). Results: During phase 1, RLS Diary attained a score of one during content validation by universal agreement. Of 34 participants, 63.6% were females with an average age of 46.6 ± 14 years. Cronbach’s alpha of the diary was 0.92. RLS diary showed the temporal change in time of onset of RLS, change in severity, and topography. The composite score from the RLS diary for week four had weak to moderate positive correlations with IRLS (week four). Conclusions: RLS Diary is a valid and psychometrically optimal tool for detailed assessment of the severity of RLS symptoms and the burden of RLS. However, there was a poor to the moderate correlation with recall-based measures of the severity of RLS.